(untitled) (Texto & Contexto, 2019)
Objective: to analyze the care actions performed by nurses during child care consultations. Method: an observational, quantitative study with 31 nurses who performed child care consultations in the Estratégia Saúde da Família of a municipality of Paraíba (Brazil). Three randomized consultations were performed by each participating nurse, totaling 93 consultations between March and July 2016, through a previously structured checklist based on the guidelines of national child health care policies containing the care actions that should be implemented by nurses. The analysis was made through descriptive statistics and chi-square test, with a significance level of 5% and cluster analysis. Results: the most common dimensions of care performed were the evaluation of immunization and iron and vitamin A supplementation; anamnesis, welcoming, physical examination/neuropsychomotor development and health education were the actions least performed by the nurses. Conclusion: nursing care in child care consultation falls short of what is established by the child health care guidelines. Continuing education interventions to qualify nurses for comprehensive child care can overcome these shortcomings